Organic Writing Assessment Dynamic Criteria Mapping in Action - Broad, Bob (University Press of Colorado, 2009)
Educators strive to create "assessment cultures" in which they integrate evaluation into teaching and learning and match assessment methods with best instructional practice. But how do teachers and administrators discover and negotiate the values that underlie their evaluations? Bob Broad's 2003 volume, What We Really Value, introduced dynamic criteria mapping (DCM) as a method for eliciting locally-informed, context-sensitive criteria for writing assessments. The impact of DCM on assessment practice is beginning to emerge as more and more writing departments and programs adopt, adapt, or experiment with DCM approaches. For the authors of Organic Writing Assessment, the DCM experience provided not only an authentic assessment of their own programs, but a nuanced language through which they can converse in the always vexing, potentially divisive realm of assessment theory and practice. Of equal interest are the adaptations these writers invented for Broad's original process, to make DCM even more responsive to local needs and exigencies. Organic Writing Assessment represents an important step in the evolution of writing assessment in higher education. This volume documents the second generation of an assessment model that is regarded as scrupulously consistent with current theory; it shows DCM's flexibility, and presents an informed discussion of its limits and its potentials.